Addressing gender-based violence FROM THE REPRODUCTIVE HEALTH/ HIV SECTOR A LITERATURE REVIEW AND ANALYSIS - GUEDES, ALESSANDRA; Ellsberg, Mary.; Bott, Sarah ([Washington, D.C. : World Bank, 2004)
"Morrison, Ellsberg, and Bott present an overview of gender-based violence (GBV) in Latin America, with special emphasis on good practice interventions to prevent GBV or offer services to its survivors or perpetrators. Intimate partner violence and sexual coercion are the most common forms of GBV, and these are the types of GBV that they analyze. GBV has serious consequences for women's health and well-being, ranging from fatal outcomes, such as homicide, suicide, and AIDS-related deaths, to nonfatal outcomes, such as physical injuries, chronic pain syndrome, gastrointestinal disorders, complications during pregnancy, miscarriage, and low birth-weight of children. GBV also poses significant costs for the economies of developing countries, including lower worker productivity and incomes, and lower rates of accumulation of human and social capital. The authors examine good practice approaches in justice, health, education, and multisectoral approaches. In each sector, they identify good practices for: (1) law and policies; (2) institutional reforms; (3) community-level interventions; and (4) individual behavior change strategies. The authors offer conclusions and recommendations for future work on gender-based violence: It is essential to focus on the prevention of GBV, not just on services for its survivors. Prevention is best achieved by empowering women and reducing gender disparities, and by changing norms and attitudes which foster violence. Interventions should employ a multisectoral approach and work at different levels--individual, community, institutional, and laws and policies. GBV may be common in the Latin America and the Caribbean region, but there are promising approaches available to begin working toward its elimination. This paper--a product of the Poverty Sector Unit, Latin America and the Caribbean Region--is part of a larger effort in the region to address issues of violence and its impact on development"--World Bank web site.
Title from PDF file as viewed on 10/22/2004.
Keywords: Women; Women; Women; Women